NEW EXPERIMENTS IN CLASSICAL DANCES: शास्त्रीय नृत्यों में नवीन प्रयोग - sharma, Sonal (International Journal of Research -GRANTHAALAYAH, 2015)
Culture is the identity of any country, region, region, village city. India is a country steeped in cultural prosperity. Culture has many elements. Among those elements, dance and music are the most powerful elements. India is the only country where the scriptures were composed for dance music. In the scriptures rules were made for music and dance drama etc. The dance music which came under these classical rules got the name of classical dance and music. There are seven classical dance styles in India. If we look at the history of each, then we will see that many changes were made in the ancient and present form of each to make the dance more visible. These new experiments were done in her dance distinctions, in her performance, in her music, in her costumes. संस्कृति किसी भी देश प्रदेश, अंचल, गाँव शहर की पहचान होती है। भारत सांस्कृतिक समृद्धि से ओतप्रोत एक देश है। संस्कृति के निर्माता कई तत्व होते हंै। उन तत्वों में नृत्य व संगीत सबसे सशक्त तत्व होते हैं। भारत एकमात्र ऐसा देश है जहाॅं पर नृत्य संगीत के लिए शास्त्रों की रचना की गई। शास्त्रों में संगीत व नृत्य नाट्य आदि के लिए नियम बनाए गए । इन शास्त्रीय नियमों के अन्तर्गत आने वाले नृत्य संगीत को शास्त्रीय नृत्य व संगीत की संज्ञा प्राप्त हुई। भारत में सात शास्त्रीय नृत्य शैलियाँ हैं। अगर प्रत्येक के इतिहास पर दृष्टि डाली जाए तो हमें दृष्टिगोचर होगा कि प्रत्येक के प्राचीन एवं वर्तमान स्वरूप में कई परिवर्तन हुए नृत्य को और दर्शनीय बनाने के लिए कई नवीन प्रयोग किए गए। यह नवीन प्रयोग उसके नर्तन भेदों में, उसके प्रदर्शन क्रम में, उसके संगीत में, उसकी वेशभूषा में किए गए।